Klotho levels and biological age acceleration: Insights from a diverse cohort of middle-aged and elderly individuals - Mengna Huang; Guoxin Huang; Chaoshen Wu; Lei Zhu; Bin Pei; Hongwei Wang; Da Qian; Puzhao Wu (PLoS ONE, 2026)
Objective Aging is characterized by progressive physiological and psychological changes, leading to decreased cellular metabolism and increased vulnerability to age-related diseases. Methods. In this study, we examined the relationship between circulating Klotho levels and biological age acceleration (BAA) in a representative cohort of middle-aged and older adults. Data were obtained from the National Health and Nutrition Examination Survey (NHANES, 2007–2010), including 5,654 participants aged 45–85 years. Serum Klotho concentrations were quantified using ELISA, while biological age was estimated with the BioAge R package. Result Linear regression analyses demonstrated a robust inverse association between log-transformed Klotho levels and BAA across all statistical models, with reductions of −1.06 (95% CI: −1.77 to −0.36, p = 0.005), −1.44 (95% CI: −2.15 to −0.73, p < 0.001), and −1.30 (95% CI: −2.20 to −0.40, p = 0.01). Consistent results were observed in logistic regression models, where higher Klotho concentrations were linked to lower odds of accelerated aging (OR = 0.72, 95% CI: 0.59–0.88, p = 0.002; OR = 0.63, 95% CI: 0.51–0.77, p < 0.0001; OR = 0.62, 95% CI: 0.46–0.84, p = 0.01). Subgroup analyses revealed significant associations in women, participants over 60 years of age, and individuals without chronic illnesses. Interaction analyses further indicated that age (p-interaction = 0.002), alcohol intake (p-interaction = 0.04), and diabetes status (p-interaction = 0.03) significantly modified the Klotho–BAA relationship. Moreover, restricted cubic spline analysis showed a non-linear L-shaped dose-response pattern, suggesting that the protective effect of Klotho becomes more pronounced above a certain threshold. Conclusion Collectively, these findings underscore the pivotal role of Klotho in the biology of aging and emphasize the importance of accounting for demographic and health-related modifiers in future investigations.